BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PADA RUMAH SAKIT UMUM DAERAH dr. SOEDONO MADIUN - Urip Purwani; Andry Irwanto (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
This study is to design strategy maps and Key Performance Indicator (KPI) within the concept of balanced scorecard in RSUD dr. Soedono Madiun. This study is expected to provide input to RSUD dr. Soedono Madiun in designing balanced scorecard, strategy maps, and KPI. The result of this study,showed the customer perspective of RSUD dr. Soedono Madiun comprises the increase of customer satisfaction, and number of patients. Internal business perspective comprises the enhancement of service and administrative quality. Learning and growth perspective comprises the improvement of power capability, facility, and employee benefits. The financial perspective comprises the enhancement of self-reliance, inc, and improvement of operational cost management of the hospital